2020
DOI: 10.1097/ju.0000000000000903.010
|View full text |Cite
|
Sign up to set email alerts
|

Mp48-10 determinants of Recurrent Urinary Tract Infection in Spinal Cord Injury Patients

Abstract: require a penile prosthesis. Surgical Complications: two patients (12.5%) showed postoperative neurapraxia, which resolved spontaneously after 12 months (Clavien I), and two other patients (12.5%) suffered extrusion of the receiver block (Clavien IIIb) We observed malfunction/damage of the external hardware in 10pt (62.5%), mostly related to operator misuse.CONCLUSIONS: Success of SARS was 87.5 % for micturition, 94% for defecation and 33% for intercourse. The main limitations were observed in caregiver-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Neither Waites et al 41 nor Edokpolo et al 40 found sex to be a predictor. However, differences in the incidence of UTI and RUTI between males and females in SCI patients undergoing CIC have been examined and found to be significantly higher in females 42 , 43 . Conversely, males have been reported to be a significant predictor of febrile UTI in individuals with SCI performing CIC 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Neither Waites et al 41 nor Edokpolo et al 40 found sex to be a predictor. However, differences in the incidence of UTI and RUTI between males and females in SCI patients undergoing CIC have been examined and found to be significantly higher in females 42 , 43 . Conversely, males have been reported to be a significant predictor of febrile UTI in individuals with SCI performing CIC 44 .…”
Section: Discussionmentioning
confidence: 99%